(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the influence of psychological violence within the family on the formation of destructive behavior in adolescents. The causes and consequences of adolescents’ destructive behavioral patterns are analyzed, highlighting the psychological mechanisms through which family disharmony and dysfunctional role structures contribute to maladaptive outcomes.